2017
DOI: 10.1111/ajr.12392
|View full text |Cite
|
Sign up to set email alerts
|

Stage of diagnosis of prostate, breast and colorectal cancer in farm residents compared with other rural and urban residents in New South Wales

Abstract: Objective: To determine if stage at diagnosis of prostate, breast and colorectal cancers differs between farm, rural non-farm and urban residents. Design: Data linkage of baseline survey information from a large cohort study, with state cancer registry records from 2006 to 2009. Setting: New South Wales, Australia. Participants: New South Wales residents enrolled in the 45 and Up Study cohort. Main outcome measures: Adjusted odds ratio of nonlocalised cancer stage was modelled using binary logistic regression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There were no clear patterns in study findings with characteristics, such as sample size or time period. While three Australian studies (8385) found no evidence of geographical differentials, three others reported that rural men were more likely to be diagnosed with advanced disease (24, 55, 86). Further discrepancies in findings were evident across the nine USA-based studies, with six reporting more advanced disease among rural residents (25, 77, 81, 82) and those with poorer access to urologists (41, 79), whereas three others found no significant differences in the rates of advanced disease between urban and rural men (39, 78, 80).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There were no clear patterns in study findings with characteristics, such as sample size or time period. While three Australian studies (8385) found no evidence of geographical differentials, three others reported that rural men were more likely to be diagnosed with advanced disease (24, 55, 86). Further discrepancies in findings were evident across the nine USA-based studies, with six reporting more advanced disease among rural residents (25, 77, 81, 82) and those with poorer access to urologists (41, 79), whereas three others found no significant differences in the rates of advanced disease between urban and rural men (39, 78, 80).…”
Section: Resultsmentioning
confidence: 97%
“…There were some variations in the definition of advanced prostate cancer with three studies each basing their classification on tumor size (77, 78, 85) or prostate cancer risk groups (79, 86, 100) and one on pathological Gleason score (90). All remaining studies used a standard cancer staging system (such as the SEER Summary stage or TNM) with Stage I-II cancers consistently referred to as localized disease, Stage III as regional disease and distant/metastatic (Stage IV) cancers as advanced (18, 24, 25, 39, 58, 64, 84, 88, 92, 102), although some collectively categorized both regional and distant cancers as advanced disease (21, 41, 55, 8083, 87, 89, 91, 9399, 101).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the majority of participants sampled in this review would not have been exposed to population‐wide screening. The majority of these studies reported that stage at diagnosis did not differ across geographic locations (Armstrong, O’Connell, Leong, Spigelman, & Armstrong, ; Baade et al, ; Beckmann et al, ; Depczynski, Dobbins, Armstrong, & Lower, ; Jong et al, ). Based on this, suggestions that late diagnosis may explain disparities in CRC survival and outcomes are not strongly supported.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the majority of participants sampled in this review would not have been exposed to population-wide screening. The majority of these studies reported that stage at diagnosis did not differ across geographic locations (Armstrong, O'Connell, Leong, Spigelman, & Armstrong, 2004;Baade et al, 2011b;Depczynski, Dobbins, Armstrong, & Lower, 2018;Jong et al, 2004).…”
Section: Key Findings Tests Of Significancementioning
confidence: 99%